2014
DOI: 10.1172/jci66287
|View full text |Cite
|
Sign up to set email alerts
|

IL-7 receptor blockade following T cell depletion promotes long-term allograft survival

Abstract: T cell depletion is commonly used in organ transplantation for immunosuppression; however, a restoration of T cell homeostasis following depletion leads to increased memory T cells, which may promote transplant rejection. The cytokine IL-7 is important for controlling lymphopoiesis under both normal and lymphopenic conditions. Here, we investigated whether blocking IL-7 signaling with a mAb that targets IL-7 receptor α (IL-7Rα) alone or following T cell depletion confers an advantage for allograft survival in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
32
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(37 citation statements)
references
References 47 publications
3
32
2
Order By: Relevance
“…Given the critical importance of IL-7 signaling for T cell homeostatic proliferation in lymphopenic conditions (12, 15, 57, 58), our data strongly suggest that the reduced IL-7Rα expression may account for the observed reduction in CD8 + T cell reconstitution. These results are in consistence with previous reports that IL-7Rα blockade with mAb inhibited lymphocyte reconstitution following T cell depletion, thus prolonging skin allograft survival, and prevented graft-versus-host disease in a mouse model of allogeneic bone marrow transplantation (59,60). The results of the WT and IL-27R -/-CD8 + T cell cotransfer experiment demonstrate the direct effect of IL-27 on this lymphocyte population (Figure 8).…”
Section: Discussionsupporting
confidence: 90%
“…Given the critical importance of IL-7 signaling for T cell homeostatic proliferation in lymphopenic conditions (12, 15, 57, 58), our data strongly suggest that the reduced IL-7Rα expression may account for the observed reduction in CD8 + T cell reconstitution. These results are in consistence with previous reports that IL-7Rα blockade with mAb inhibited lymphocyte reconstitution following T cell depletion, thus prolonging skin allograft survival, and prevented graft-versus-host disease in a mouse model of allogeneic bone marrow transplantation (59,60). The results of the WT and IL-27R -/-CD8 + T cell cotransfer experiment demonstrate the direct effect of IL-27 on this lymphocyte population (Figure 8).…”
Section: Discussionsupporting
confidence: 90%
“…Finally, one potential advantage of IL-7Rα-targeted therapy is that it specifically spares Tregs over effector T cells (21), based on a high differential expression level (14,15). We found that IL-7 was able to dose-dependently induce STAT5 phosphorylation in Tregs, in spite of the low expression level of its receptor on these cells, but did not induce α 4 β 7 overexpression in contrast to its effect on effector T cells ( Figure 5D).…”
Section: Resultsmentioning
confidence: 76%
“…Human infants with IL-7Rα mutations have severe T cell lymphopenia necessitating bone marrow transplantation (82). In contrast to most studies performed in rodent models where IL-7R blockade also induces broad lymphodepletion (21), administration of high doses of anti-IL-7Rα antagonistic mAb in baboons (83), cynomolgus monkey (84), or marmosets (85) did not induce lymphopenia or a significant decrease in peripheral T lymphocyte numbers. Similarly, early clinical results from phase I trials with 2 different antagonist anti-IL-7Rα mAbs, in healthy volunteers (GSK2618960; NCT02293161, ClinicalTrials.gov) or in type 1 diabetic adult patients (PF-06342674; NCT02038764), did not demonstrate induction of lymphopenia (86).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In the context of islet transplantation, blocking IL-7Rα protected allogeneic islet grafts 126 from rejection in streptozotocin (STZ)-induced diabetic mice (Mai et al, 2014). Yet again, protection was associated with reduced T-cell IFN-γ production and PD-1 expression.…”
mentioning
confidence: 99%